Leaf Venation and Morphology Help Explain Physiological Variation in Yucca brevifolia and Hesperoyucca whipplei Across Microhabitats in the Mojave Desert, CA - Jolly, Amber R.; Zailaa, Joseph; Farah, Ugbad; Woojuh, Janty; Libifani, Félicia Makaya; Arzate, Darlene; Caranto, Christian Alex; Correa, Zayra; Cuba, Jose; Calderon, Josephina Diaz; Garcia, Nancy; Gastelum, Laura; et al. (Frontiers in Plant Science, 2021)
Different microclimates can have significant impact on the physiology of succulents that inhabit arid environments such as the Mojave Desert (California). We investigated variation in leaf physiology, morphology and anatomy of two dominant Mojave Desert monocots, Yucca brevifolia (Joshua tree) and Hesperoyucca whipplei, growing along a soil water availability gradient. Stomatal conductance (gs) and leaf thickness were recorded in the field at three different sites (northwestern slope, southeastern slope, and alluvial fan) in March of 2019. We sampled leaves from three individuals per site per species and measured in the lab relative water content at the time of gs measurements, saturated water content, cuticular conductance, leaf morphological traits (leaf area and length, leaf mass per area, % loss of thickness in the field and in dried leaves), and leaf venation. We found species varied in their gs: while Y. brevifolia showed significantly higher gs in the alluvial fan than in the slopes, H. whipplei was highest in the south-eastern facing slope. The differences in gs did not relate to differences in leaf water content, but rather to variation in number of veins per mm2 in H. whipplei and leaf width in Y. brevifolia. Our results indicate that H. whipplei displays a higher water conservation strategy than Y. brevifolia. We discuss these differences and trends with water availability in relation to species’ plasticity in morphology and anatomy and the ecological consequences of differences in 3-dimensional venation architecture in these two species.